PENGARUH BERPIKIR KREATIF DAN KOMUNIKASI MATEMATIKA DENGAN METODE LEARNING CYCLE (Universitas PGRI Sumatera Barat, 2019)
ABSTRACT Based on the results of observations made the reality of the learning conditions of mathematics at Daha 1 Pawyatan Middle School Kediri focused more on teacher lectures. So that teachers play an active role, while students tend to be passive. Students only listen, take notes and work on the questions given by the teacher. In addition, learning like this also causes the mathematics learning process to become less communicative. As a result the value of students becomes less optimal and other learning behaviors such as a pleasant classroom atmosphere and communicative students in learning almost do not appear, for that variation in the learning process in a school is needed. As an effort to improve creative thinking and mathematical communication, the right learning method (learning cycle method) is needed, so that learning becomes more effective and maximum learning outcomes. The approach used in this study is a quantitative approach with the design of Posstest-Only Control Design. The population in this study were all class VIII students at Daha Pawyatan Middle School 1 Kediri Academic Year 2018/2019 and with cluster random sampling sampling techniques this study sample. Data collection is obtained by test techniques. The collected data were analyzed using the t-test. Based on testing the hypothesis, it can be concluded that. (1) the learning cycle method influences students' creative thinking abilities. This is evidenced by thcount 7,395 and the value of sig. (2-tailed) of 0,000 <0,05. (2) The learning cycle method influences students' mathematical communication. This is proven by tcount 4,716 and sig. (2-tailed) of 0,000 <0,05. From the results of the study which showed that the value of mathematics communication skills of students was 56.3% in the good category and the average creative thinking ability of students was 73.59. Based on the results of the study, it can be concluded that the learning cycle method influences students' creative thinking and mathematical communication, so it is recommended for teachers that the learning cycle method can be used as an alternative learning medium for teachers to improve creative thinking and mathematical communication of students Key Words: learning cycle method; creative thinking; mathematical communication